COLLEGE STUDENTS SELF-REGULATED LEARNING STRATEGIES IN ACADEMIC WRITING AND WRITING PERFORMANCE: CORRELATIONAL STUDY - Rochmah, Miftaachur (RETAIN, 2021)
This study aimed at exploring further the correlation between college students’ self-regulated learning strategies and writing performance in the EFL context. Additionally, this present study also investigated the most frequently used strategies of college students’ while completing their written tasks. Writing Strategies for Self-Regulated Learning Questionnaire (WSSRLQ) was administered to 72 junior students majoring in English Education at one of the state universities in Surabaya. The result reported that learners rather used social-behavioral Strategies (M = 3.90), followed by motivational strategies (M = 3.84), cognitive strategies (M = 3.75), and metacognitive strategies (M = 3.74). This study also revealed that there was a medium correlation between self-regulated learning strategies and writing performance (p = .000, r = 0.481). Moreover, the result also showed a correlation between the dimensions of self-regulated learning with writing performances namely metacognitive, cognitive and social-behavioral strategies, yet there is no correlation between motivational strategies and writing performance. Keywords: EFL, Self-regulated learning strategies, Writing Performances